Asymmetric Innovation Agreements under Environmental Regulation - Naoto Aoyama; Emilson C.D. Silva (Center for Economic Studies and ifo Institute (CESifo), 2017)
In a domestic market, a duopoly produces a homogeneous final good, pollution, pollution abatement and R&D. One of the firms (foreign) has superior technology. The government regulates the duopoly by levying a pollution tax to maximize domestic welfare. We consider the potential implementation of three innovation agreements: cooperative research joint venture (RJV), non-cooperative RJV and licensing. In the cooperative (non-cooperative) RJV, the firms (do not) internalize R&D spillovers. We show that, for the domestic firm, the cooperative RJV dominates and licensing is the least desirable alternative. Although licensing is dominant for the foreign firm, it is not implementable. Both RJVs are implementable. While the non-cooperative RJV is more likely the greater the degrees of asymmetry (in terms of efficiency and R&D spillover rates) between the firms, the cooperative RJV is more likely the lower the degrees of asymmetry. Implementation of both types of RJVs improve the competitiveness of the domestic firm and welfare. A subsidy policy that induces the foreign firm to accept a feasible cooperative RJV when it strictly prefers a feasible non-cooperative RJV is always welfare improving.
Keywords: D43; D62; F23; L13; L24; L51; Q55; Q58; 330; environmental regulation; innovation; research joint ventures; licensing